Faktor Aktivitas Fisik, Asupan Protein, dan Keragaman Gizi dengan Status Gizi Remaja di Kabupaten Sidoarjo: Studi Cross-Sectional - Hilma Nahlah Faradisah; Dwi Rukma Santi; Eko Teguh Pribadi (HB PRESS, 2026)
Adolescents are an age group vulnerable.to nutritional problems due to changes in lifestyle, diet, and physical activity. This study analyzed the relationship between physical activity, protein intake, and nutritional diversity with the nutritional status of adolescents at SMA PGRI 1 Sidoarjo. The study design used a cross-sectional approach with 120 students as respondents. Data collection used a structured questionnaire and SQ-FFQ, while nutritional status was determined based on BMI. Data analysis was performed using the Spearman correlation test. The results showed that most adolescents had high physical activity (61.70%), adequate protein intake (47.50%), and diverse nutritional diversity (55.80%). The nutritional status of adolescents was mostly in the normal category (40.00%). The results of the Spearman correlation test showed that there was no relationship between physical activity and nutritional status (p value = 0.242; p > 0.05), there was a relationship between protein intake and nutritional status (p value = 0.024; p < 0.05), there was a relationship between nutritional diversity and nutritional status (p value = 0.000; p < 0.05). It can be concluded that the quality of food intake, especially protein and nutritional diversity in adolescent nutritional status is important.